Pendidikan Pluralisme dalam Al-Quran (Reformulasi Pendidikan Islam Berbasis Resolusi Konflik) - Prabowo Adi Widayat (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2016)
Education becomes a mediator of change in every line of life, with him, the man directed and taught how to harness diversity on this earth which contained natural and socio-cultural environment. The process of human civilization continually experience the friction or unrest caused by avariety of things. Both of these things always become a barrier in realizing the benefit and convenience of life for mankind. On the other hand, educational pluralism spearheading peace mission and benefit in the face of this earth. Furthermore, the Qur’an describes educational pluralism proportionately and solutif, with it also produces an idea of conflict resolution is needed and will become a customary or inevitability to formulate the repeated teachings of Islam through the system and the process of education is good and correct.